1995
DOI: 10.1177/036354659502300621
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankle Stabilizers on Athletic Performance

Abstract: The ankle is the site of more than one third of all injuries that occur to male basketball players. Although ankle bracing may prevent injury, many players believe that braces restrict athletic performance. This belief discourages use of braces and obviates the injury protection that bracing provides. The objectives of this study were to 1) determine whether athletic performance (in four basketball-related activities) was affected by three ankle brace designs (Universal, Kallassy, and Air-Stirrup ankle trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 21 publications
4
32
0
1
Order By: Relevance
“…In addition, MacKean et al [13] reported that tape and several types of ankle brace all impaired vertical jumping and running performance. In contrast, Pienkowski et al [17] reported that other types of braces did not. Different taping techniques, experimental protocols, type of motor skills used, or loosening of materials during testing may have contributed to these disparate findings.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, MacKean et al [13] reported that tape and several types of ankle brace all impaired vertical jumping and running performance. In contrast, Pienkowski et al [17] reported that other types of braces did not. Different taping techniques, experimental protocols, type of motor skills used, or loosening of materials during testing may have contributed to these disparate findings.…”
Section: Discussionmentioning
confidence: 93%
“…Many studies have observed the effect of the bracings in the ankle muscles during sportive activities (8)(9)(10) . Hopper et al (8) investigated the electromyographic activity of the gastrocnemius, the tibial anterior and the peroneus longus muscles during the jump using adhesive tape, and jump using bracing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MacKean [15] reported that tape and three different ankle braces (Swede-O-Universal, Active Ankle, Aircast brace), all impaired vertical jumps and running performance. In contrast, Pienkowski et al [21] reported that braces (Universal, Kellassy, Aircast brace) did not Fig. 4 Lateral displacement of the centre of pressure (COP) at touchdown caused by lace-up cloth brace and taping may result in larger lever arm, producing pronation moment.…”
Section: Discussionmentioning
confidence: 98%